Review of the genus Heteropogon Loew, 1847 (Diptera: Asilidae) from Russia and Central Asia, with description of two new species - Sakhvon, Vital V.; Lelej, Arkady S. (Zootaxa, 2018)
Nine species of genus Heteropogon Loew, 1847 are reviewed. Heteropogon ater Sakhvon sp. nov. (Kazakhstan, Tajikistan) and H. hiemalis Sakhvon sp. nov. (Turkmenistan) are described and illustrated. A new synonymy is proposed for Heteropogon filicornis (Loew, 1871) = Cyrtopogon leleji Lehr, 1998, syn. nov. The status of Heteropogon lugubris mesasiaticus Lehr, 1970 is upgraded to species level that of mesasiaticus. The distribution of some species is increased. A key to males of the species is given.